Factors that may be influencing the rise in prescription testosterone replacement therapy in adult men: a qualitative study. (2nd April 2016) - Mascarenhas, Alekhya; Khan, Sobia; Sayal, Radha; Knowles, Sandra; Gomes, Tara; Moore, Julia E.
Abstract: Objective : To explore and describe the factors that may be influencing the rise of prescribing and use of testosterone replacement therapy (TRT) in adult men. Design : A rapid qualitative research design using semi-structured interviews with providers and patients. Setting : Ontario, Canada. Participants : Nine men who have used TRT (referred to as "patients"), and six primary care clinicians and seven specialists (collectively referred to as "providers") who prescribed or administered TRT. Method : Patients' and providers' perspectives were investigated through semi-structured interviews. A purposive sampling approach was used to recruit all participants. We conducted qualitative analysis using the framework approach for applied health research. Main findings : Participants perceived the following factors to have influenced TRT prescriptions and use in adult men: provider factors (diagnostic ambiguity of age-related hypogonadism and beliefs about appropriateness of TRT) and patient factors (access to information on TRT and drug seeking behavior). They perceived that these factors have perpetuated a rise in prescription in the absence of clear clinical guidelines and unclear research evidence on the safety and efficacy of TRT. Conclusion : The findings of this study highlight that much work still needs to be done to improve diagnostic accuracy and encourage appropriate TRT prescription in adult men. In addition, both patients and providers need more information about the risks and long-term effects of TRT in men.